2019
DOI: 10.1186/s42483-019-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide resistance of Botrytis cinerea from strawberry to procymidone and zoxamide in Hubei, China

Abstract: Gray mold, caused by Botrytis cinerea, is one of the most destructive diseases of strawberry in China. For resistance monitoring, 198 B. cinerea isolates were collected from strawberry greenhouses at 10 locations in Hubei Province. The isolates were screened for resistance to fungicides procymidone and zoxamide. In mycelium growth assays for procymidone, the mean values of effective concentration at which mycelium growth is inhibited by 50% (EC 50) for sensitive (Pro S) and resistant (Pro R) isolates were 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 62 publications
(114 reference statements)
1
25
0
Order By: Relevance
“…All strains were sensitive to iprodione from 0.07 to 0.87 µ g/mL with an average of 0.47 µ g/mL. These results are similar to B. cinerea collected from strawberry, a procymidone and zoxamide sensitive strain from Hubei province having EC50 value of 0.25 µg/mL and 0.360 µg/mL, respectively [22]. No 100% sensitive strain was discovered in our collected samples because iprodione is a site specific fungicide with high efficacy, less toxicity and lower application rate.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…All strains were sensitive to iprodione from 0.07 to 0.87 µ g/mL with an average of 0.47 µ g/mL. These results are similar to B. cinerea collected from strawberry, a procymidone and zoxamide sensitive strain from Hubei province having EC50 value of 0.25 µg/mL and 0.360 µg/mL, respectively [22]. No 100% sensitive strain was discovered in our collected samples because iprodione is a site specific fungicide with high efficacy, less toxicity and lower application rate.…”
Section: Discussionsupporting
confidence: 71%
“…The point mutation in the two components of histidine kinase genes (Bcos1) responsible for resistance to iprodione has been identified in B. cinerea isolated from strawberry fruit [ 21 ]. Substitution at codon I365 was dominant to cause resistance against iprodione among various strains of B. cinerea [ 22 , 23 , 24 ]. BcNoxA and BcNoxB catalytic subunits are responsible for pathogenicity and the formation of spores, which provide a favorable environment to fungal sclerotic to survive under adverse environmental conditions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, infection control was managed by chemical fungicides [ 56 ], which, in itself, proves to be a problem due to residues in tomato fruits and the risk of toxicity for consumers [ 57 , 58 ]. Additionally, recent evidence showed that B. cinerea has already acquired resistance to many of the commonly used fungicides [ 59 ]. Apart from the effective reduction of tomato plant leaf destruction by mold-induced necrosis in the presence of PAFC, we also proved the tolerance of tomato leaves and M. truncatula seedlings to PAFC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of effectiveness of MBCs caused by the build‐up of resistance over the last 50 years has been noticed worldwide. In general, resistant isolates possess a high resistance (HR) phenotype (Adnan et al ., 2019), which is associated with several point mutations in the β‐tubulin target gene (Fan et al ., 2016; Adnan et al ., 2019). Furthermore, they are as fit as wild‐type isolates (Leroux, 2004) and often remain dominant in a population even in the absence of sprays for several years (De Miccolis Angelini et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated that resistance to DCs is diffuse in the country on both crops and confirmed that mutations in the BcOs1 target gene are most predominant at codon 365, with most DC‐resistant isolates showing a low level of resistance (LR; Oshima et al ., 2006). The double mutation Q369P and N373S in the BcOs1 gene, which was recovered in only three resistant isolates in our study, has always been associated with isolates with a moderate level of resistance (MR; Oshima et al ., 2006), although recently low‐resistant (LR) phenotypes in China possessed this pair of SNPs (Adnan et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%